Analysis of the Impact of Motor Vehicle Tax Collection Option on Regional Revenue - Fitriana, Annisa (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study analyzes the impact of implementing motor vehicle tax and motor vehicle title transfer tax on the regional revenue of districts/cities in East Java. Using a quantitative approach and comparative analysis method, the study compares revenue-sharing schemes based on the 2023 realization data for motor vehicle tax and title transfer tax. Simulation results indicate that the implementation of surcharges (Opsen) increases the aggregate revenue of districts/cities by 10.08% but decreases provincial revenue by IDR 0.41 trillion. Surabaya City experiences the highest revenue increase of 73.25%, while Pacitan suffers the deepest decline. These differences are due to the number of registered motor vehicles in each region. This situation has the potential to create horizontal revenue disparities among regions. Nevertheless, the results align with the objectives of fiscal decentralization, which aim to strengthen local taxing power. However, an appropriate cost-sharing mechanism is needed to maintain the quality of motor vehicle tax and title transfer tax collection services.